Description of the immature of Podisus graziae Brugnera, Roell & Lemaître, 2021 (Heteroptera: Pentatomidae: Asopinae) - Sampaio, Vinicius Gomes; Paim, Marcelo Reginato; Limberger, Guilherme Martins; Brugnera, Ricardo (Zootaxa, 2023)
As predaceous insects, the Asopinae have a great economic importance. The knowledge about the development of the species is essential for use in biological control programs. However, only 1% of the Neotropical Asopinae species have the immature stages known. In this work we describe the egg and the five nymphal stages of Podisus graziae Brugnera, Roell & Lemaître, 2021 using light and scanning electron microscopy. The results show that P. graziae eggs and nymphs present unique characters which are not observed in other species of the genus and subfamily. As other Podisus species, the egg present long aero-mycropilar processes, however, the chorion and operculum have a ring of minute spine-like projections. As main diagnostic characters of nymphs, the iridescent coloration of head, thorax and abdominal plates, and a pair of yellow spots in the pronotum and anterior region of abdomen are noticed.